VLF DALGA YAYILIMINA GÜNEŞ AKTİVİTESİNİN ETKİLERİNİN İNCELENMESİ - AKDOĞAN, TAYFUN (Fırat Üniveristesi, 2013)
SUPER SID olarak bilinen sistem aslında uzay hava durumunu izleme sistemi olarak bilinir. Güneş patlamaları Yer iyonküresinde ani değişikliklere sebep olurlar. Bu etkiler Yer-iyonküre dalga kılavuzunda yayılan VLF sinyalleri ile tespit edilirler. Fen Fakültesi Fizik Bölümü Elektromanyetik Dalgalar Laboratuvarında bir Süper SID sistemi kurulmuştur. Bu sistem farklı VLF vericilerinden gelen zamana bağlı sinyal şiddetlerini kaydeder. Bizim Süper SID sistemi ile 2013 Şubat, Mart ve Nisan aylarında C (küçük) ve M (orta) olarak sınıflandırılan Güneş patlamaları tespit edilmiştir. Güneş patlamalarının etkisi alıcıya yakın olan VLF vericilerinde (TBB,DHO,NOV,RJH99) uzak olan vericilerden (NAA,NWC,NLK) daha net bir şekilde gözlenmektedir. Anahtar Kelimeler: VLF, İyonküre, Güneş Parlaması

SUPER SID system is actually known as the Space Weather Monitoring System. Solar flares cause sudden disturbances at the Earth?s ionosphere. These effects are detected by the VLF (Very Low Frequency) signals which is propagated at the Earth-Ionosphere wave guide. A SUPER SID system was setup at the Electromagnetic wave Lab, Physics Department, Science Faculty, Elazig. This system records the time-dependent signal strengths of the different VLF transmitters. Solar flares which are classified as C (small) and M (middle) are identified by our SUPER SID system during the February, March, April, 2013. The effect of solar flares are seemed more clear on the VLF transmitters (TBB,DHO,NOV,RJH99) which are nearest to the recevier than far transmitters (NAA,NWC,NLK). Key Words: VLF, Ionosphere, Solar Flare
Investigation of the effects of the solar activities on VLF wave propagation
Keywords: Fizik ve Fizik Mühendisliği